Aplicación de los diagramas bioclimáticos a la provincia de lérida: determinación de los parametros bioclimáticos para las masas de QUERCUS ILEX BALLOTA Y QUERCUS FAGINEA - Rovirola, D.; Alcazar, J.; Peman, J. (III Congreso Forestal Español Congreso, 2001)
The present work tries to characterize the different bulks of Quercus ilex and Q. .faginea that are distributed all over the province of Lérida through the utilization of the Diagramas bioclimáticos. Results are intended to give criteria for the utilization of these species in reforestation projects.
The following values have no corresponding Zotero field: periodical: III Congreso Forestal Español Congreso issue: 1987 pub-location: Granada
Keywords: diagramas bioclimáticos; forestation; Quercus faginea; Quercus ilex ballota